PENGEMBANGAN USAHA PENJAHIT RUMAHAN DI DESA BACEM KABUPATEN BLITAR MELALUI MANAJEMEN PRODUKSI, KEUANGAN DAN PEMASARAN - Ayuswantana, Alfian Chandra; Suprianti, Lilik; Perwitasari, Rida; Pradhani, Fastha Aulia (Universitas Mataram, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are important for economic development for several reasons including being the leading employer and contributing to the growth of villages and towns. However many MSMEs are hard to grow due to limited capital, skills, and lack of support. This community service project was done together with Hani Jahit, a home industry of clothes production located in the village of Bacem, Blitar Regency. Hani Jahit faces capital limitations where the sewing machine in use is no longer suitable. There is no order in the production area and there is a failure in the management in functioning the business. Also, there is no record of income and expenses. The main objective of this community service program was to make a positive contribution to the productivity of the partner business with the view of improving its growth and development. The strategies used were to survey the partner and offer training and support in production, financial, and marketing. In addition, the team of community services offered a new sewing machine of better quality than the previous one, rearranged the place of production, and placed a business sign. By so doing, through this community service undertaking, Hani Jahit increased production by twofold. The fact is this outcome proves that the interventions used by the Abdimas team helped to promote business growth.